The problem of determining value orientations in modern psychology - I. A. Bakushkin; I. M. Ilicheva (Вестник университета, 2024)
The article analyzes approaches to value orientations study in Russian and foreign psychology. The definition of value orientations based on the reflection, activity, activity, determinism principles has been clarified. The features of the approach to the value orientations study in Russian psychology are represented by three directions – philosophical, concrete-scientific and psychological. The features of the value orientations study in foreign psychology have been presented, where the main attention is paid to the problems of personality typology on the basis of its value orientations and their role in the activity motivation. Each person is guided by what is considered by him as important, essential, and strives to achieve what acquires for him subjective value. Within the framework of general psychology and personality psychology, we always mean individually significant values, on which a person is oriented, – value orientations. A refined definition of value orientations as a mental dimension of the reflected objective reality in the form of subjective significance of its components, which is analyzed in the directionality of the subject’s activity and structured in accordance with the level of its spiritual and moral component, has been given.